Campylobacteremia in stage IV gliosarcoma with bevacizumab treatment - Ping Liu (Journal of Community Hospital Internal Medicine Perspectives, 2012)
Primary campylobacter enteritis with secondary bacteremia was diagnosed in an immunocompromised patient with stage IV gliosarcoma. She developed mild diarrhea followed by systemic symptoms with transient generalized weakness and fever. She was treated with azithromycin and had a full recovery and without relapse through 2 months of follow-up. Her diagnosis was confirmed by a positive stool culture for Campylobacter sp. and blood culture for Campylobacter jejuni/coli.